An analysis of english language teaching strategies: Basis for interactive teaching and learning activities - Sulhairi Sulhairi; Taufiq Kurniawan (Program Studi Tadris Bahasa Inggris Institut Studi Islam Sunan Doe, 2022)
A study on Analysis of English Language Teaching Strategies is a type of quantitative and qualitative research. This research took place at SMA 1 Pengasih, Kulonprogo. Specifically, this research was conducted in the tenth grade of the English Class of SMA 1 Pengasih, Kulongprogo. This study attempted to analyze the ELT strategies based a documented classroom activity. Qualitative research focused on phenomena that occurred in natural settings and the data were analyzed without the use of statistics. Meanwhile, quantitative data, which is considered to be closed-ended questions, was typically gathered through attitude, behavioral, and performance instruments, as well as checklists in an attempt to answer narrow questions and explain the relationships between variables. The following assumptions guided this study were a) there were ELT strategies utilized by Indonesian teachers as shown in the recorded video clip, b) interactive ELT learning activities could be developed in ELT classroom, c) interactive learning activities could be developed consistently with the criteria used in the study.